Pigmentation disorders in three specimens of spiny dogfish, Squalus acanthias Linnaeus, 1758, from the Gulf of Venice, northern Adriatic Sea - Jacopo Bernardi; Licia Finotto; Giusy Catalano; Valentina Crobe; Alessia Cariani; Alice Ferrari (Journal of Fish Biology, 2026)
This study reports three cases of pigmentation disorders in Squalus acanthias from the Gulf of Venice. Two specimens exhibited spotless phenotypes, whereas one exhibited hypermelanism. Morphological assessments were conducted for two individuals, alongside genetic analysis of mitochondrial genes to determine phylogeographic relationships. Both specimens belonged to the South Pacific/Atlantic/Mediterranean haplogroup, with the first one associated with the main haplotype and the second one linked to a rarer haplotype. This study emphasizes the need for proper identification based on morphology and genetics when pigment disorders hinder a clear‐cut species assignment.

Surveying Shared Marine Resources at a Regional Scale: Connectivity and Differentiation of Round Sardinella in Eastern Mediterranean - Alice Ferrari; Giusy Catalano; Valentina Crobe; Alessia Cariani; Emre Keskin; Pierluigi Carbonara; Loredana Casciaro; Reda M. Fahim; Sharif Jemaa; Savaş Kılıç; Myriam Lteif; Abdalnasser S. H. Madi; et al. (Fishes, 2026)
The round sardinella (Sardinella aurita Valenciennes, 1847) is a widely distributed migratory pelagic fish inhabiting the Mediterranean Sea and the eastern Atlantic coasts. The species is heavily exploited and represents a valuable resource for global fisheries. In the Mediterranean area, uptakes of round sardinella are particularly high in the Ionian and Levant regions, where landings have shown fluctuating yet significant peaks in recent decades. Given its migratory nature, understanding the connectivity among populations is crucial for delineating appropriate fishery management units. Previous studies employing morphometric, meristic, and molecular analyses have yielded mixed results regarding population structuring. Here, the genetic differentiation among Eastern Mediterranean S. aurita populations was investigated using a multi-marker approach: the mitochondrial cytochrome c oxidase subunit I (COI), cytochrome b (CytB), control region (CR), and 16S ribosomal RNA (16S rRNA), and seven species-specific nuclear simple sequence repeats (SSRs). Overall, the results indicate high genetic diversity coupled with weak population structuring across the Eastern Mediterranean. These analyses aim at clarifying stock boundaries towards supporting sustainable management strategies at a regional scale for this ecologically and economically important species.

A line with no hook: longline-associated passive eDNA samplers for deep-sea fish monitoring - Martina Spiga; Valentina Crobe; Alice Ferrari; Giulia Maiello; Elia Bueloni; Elisabetta Cilli; Tommaso Russo; Simone Di Crescenzo; Rita Cannas; Giusy Catalano; Corrado Piccinetti; Stefano Mariani; et al. (Marine Environmental Research, 2026)

Applying a regional certification scheme for aquatic invasive species fishery: The case of blue crab (Callinectes sapidus) in the northern Adriatic Sea - Sara Bonanomi; Simone Libralato; Loretta Malvarosa; Karolina Maria Czechowska; Giulia Sandalli; Alessia Cariani; Alice Ferrari; Ernesto Azzurro; Giuseppe Scarcella (Marine Policy, 2025)

High Connectivity in the Deep-Water Pagellus bogaraveo: Phylogeographic Assessment Across Mediterranean and Atlantic Waters - Martina Spiga; Giusy Catalano; Federica Piattoni; Alice Ferrari; Carolina Johnstone; Kenza Mokhtar-Jamaï; Montse Pérez; Fabio Fiorentino; Manuel Hidalgo; Alessia Cariani (Fishes, 2025)
The Blackspot Seabream, Pagellus bogaraveo, is a commercially valuable species widely distributed in the northeastern Atlantic and Mediterranean. Its biology makes it vulnerable to overfishing, but its population structure and ontogenetic migration strategy remain unclear. Building on previous work based on microsatellite markers, we expanded the investigation by analysing the mitochondrial Control Region (CR) to complement nuclear data. We analysed 199 specimens from 13 sites and combined the new CR sequences with 129 published records to achieve the broadest coverage in terms of biogeographic and genetic data. We calculated genetic diversity and performed AMOVA, pairwise ΦST comparisons, and multivariate analyses. Eighty-eight haplotypes were identified, showing high haplotype diversity (Hd = 0.767–0.945) and moderate nucleotide diversity (π = 0.0026–0.0054). Most genetic variation occurred within populations, and overall analyses indicated genetic homogeneity. However, pairwise analysis and AMOVA confirmed significant differentiation of the Azores population. These results confirm extensive genetic connectivity throughout the Atlantic–Mediterranean range of P. bogaraveo, likely due to a combination of large larval dispersal and a common spawning migration strategy, but identify the Azores as a genetically distinct unit. This highlights the need to consider both large-scale connectivity and local divergence in fisheries management.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Poly(biphenyl-piperidinium)/poly(biphenyl-trifluoroacetophenone) random and block copolymers enabling highly stable anion exchange membranes for water electrolysis - Tommaso Caielli; Alessandro Raffaele Ferrari; Diego Stucchi; Chiara Ferrara; Angela Caprì; Irene Gatto; Vincenzo Baglio; Alice Pancaldi; Adele Sassella; Stefania Zappia; Alberto Giacometti Schieroni; Piercarlo Mustarelli (Chemical Engineering Journal, 2025)

Fishing in the gene-pool: implementing trawl-associated eDNA metaprobe for large scale monitoring of fish assemblages - Giulia Maiello; Andrea Bellodi; Alessia Cariani; Paolo Carpentieri; Laura Carugati; Davide Cicala; Alice Ferrari; Cristina Follesa; Alessandro Ligas; Paolo Sartor; Alice Sbrana; Peter Shum; et al. (Reviews in Fish Biology and Fisheries, 2024)
Marine biodiversity monitoring in the Mediterranean’s increasingly threatened ecosystems is crucial for effective ecosystem conservation and management. Here, we leveraged the Mediterranean International Trawl Survey program (MEDITS) to implement eDNA sampling through the recently tested ‘metaprobe’ procedure and characterize fish assemblages in three separate areas off the Italian coasts: Northern Adriatic Sea (NoAS), Ligurian and Northern Tyrrhenian Sea (LNTS), and Sardinian Sea (SaS). By combining the information from two homologous mitochondrial 12S metabarcodes––i.e., Elas02 and Tele02 targeting elasmobranchs and teleosts, respectively––we identified 108 species, over 60% of which overlapped with those caught by the trawl net. We produced an accurate reconstruction of fish community composition of the examined sites, reflecting differences in species assemblages linked with both geographic area and depth range. Metaprobe eDNA data consistently returned a biodiversity ‘bonus’ mostly consisting of pelagic taxa not captured through bottom trawl surveys, including rare and endangered taxa (e.g., elasmobranchs). Overall, the spatial characterisation of the assemblages across the surveyed areas was better delineated and more robust using eDNA metabarcoding than trawl data. Our results support the operationalisation of the metaprobe as a simple, inexpensive, versatile sampling tool, in association with pre-existing ship surveys, to overcome many of the limitations of marine data collection and strengthen marine management.

Environmental DNA Metabarcoding of Cephalopod Diversity in the Tyrrhenian Deep Sea - Martina La Torre; Alex Cussigh; Valentina Crobe; Martina Spiga; Alice Ferrari; Alessia Cariani; Federica Piattoni; Federica Costantini; Silvia Franzellitti; Alberto Pallavicini; David Stanković; Sergio Stefanni (Journal of Marine Science and Engineering, 2024)
The deep sea, the largest biome on Earth, is the least explored and understood. This lack of knowledge hampers our ability to understand and protect this important environment. In this study, water and sediment samples were collected at different depths in the central Mediterranean (224–780 m), specifically, within the Dohrn Canyon and the Palinuro Seamount, to investigate the diversity of cephalopods and establish a baseline knowledge of their distribution in these sites to preserve their habitats and estimate the impacts of human-driven environmental changes. Key taxa identified included Heteroteuthis sp., Loligo sp., and Histioteuthis sp., which were the most abundant across all sampling stations. A low overlap in species detection was observed between water and sediment samples, confirming previous findings that the typology of environmental matrices used in eDNA metabarcoding has a significant impact on the organisms detected and, therefore, the integrated use of different matrices to better represent local biodiversity is recommended. Furthermore, this study highlights the limitations posed by gaps in reference databases, particularly for deep-sea organisms, and addresses these by emphasising the need for improved multi-marker approaches and expanded reference databases to enhance the accuracy of eDNA-based biodiversity assessment.

Herbicide and nutrient monitoring in surface waters and groundwater of a paddy district in northern Italy - Alice Tediosi; Federico Ferrari; Diego Voccia; Olfa Gharsallah; Lucrezia Lamastra; Lucio Botteri; Riccardo Rossi; Tommaso Ferrari; Nicola Ballerini; Giulio Luca Cristian Gilardi; Arianna Facchi (Environmental Science and Pollution Research, 2024)

Updating knowledge on the Critically Endangered white skate Rostroraja alba (Lacepède, 1803) through the first record in North-East Sardinian coastal waters - ANDREA BELLODI; SIMONE DI CRESCENZO; PIERLUIGI CARBONARA; VALENTINA CROBE; ALICE FERRARI; ANTONELLO MULAS; CRISTINA PORCU; MARIA CRISTINA FOLLESA; RITA CANNAS (Mediterranean Marine Science, 2024)
The white skate Rostroraja alba has exhibited a declining trend similar to that of several large-bodied batoids in recent years. Consequently, it has been classified as Critically Endangered in European waters by the International Union for the Conservation of Nature. The presence of this species in Sardinian seas (central-western Mediterranean Sea) was recently hypothesised following the discovery of a hatched eggcase. Our findings confirmed this hypothesis through the discovery of another eggcase (this time unhatched) and, more importantly, the capture of an immature female (total length 131.2 cm) which was estimated to be 6 years old. Moreover, molecular analysis demonstrated that the new eggcase and the specimen did not share the same mother, thus suggesting the presence of a resident population, albeit likely small, of the species in the Sardinian seas.

A multidisciplinary approach to describe population structure of Solea solea in the Mediterranean Sea - Rachele Corti; Elisabetta Piazza; Enrico Nicola Armelloni; Alice Ferrari; Audrey J. Geffen; Gregory E. Maes; Francesco Masnadi; Castrense Savojardo; Giuseppe Scarcella; Marco Stagioni; Fausto Tinti; Alex Zemella; et al. (Frontiers in Marine Science, 2024)
Investigating marine species population structure in a multidisciplinary framework can reveal signatures of potential local adaptation and the consequences for management and conservation. In this study we delineate the population structure of common sole ( Solea solea ) in the Mediterranean Sea using genomic and otolith data, based on single nucleotide polymorphism (SNPs) markers, otolith shape and otolith trace element composition data. We correlated SNPs with environmental and spatial variables to evaluate the impact of the selected features on the actual population structure. Specifically, we used a seascape genetics approach with redundancy (RDA) and genetic-environmental association (GEA) analysis to identify loci potentially involved in local adaptation. Finally, putative functional annotation was investigated to detect genes associated with the detected patterns of neutral and adaptive genetic variation. Results from both genetic and otolith data suggested significant divergence among putative populations of common sole, confirming a clear separation between the Western and Eastern Mediterranean Sea, as well as a distinct genetic cluster corresponding to the Adriatic Sea. Evidence of fine-scale population structure in the Western Mediterranean Sea was observed at outlier loci level and further differentiation in the Adriatic. Longitude and salinity variation accounted for most of the wide and fine spatial structure. The GEA detected significant associated outlier loci potentially involved in local adaptation processes under highly structured differentiation. In the RDA both spatial distribution and environmental features could partially explain the genetic structure. Our study not only indicates that separation among Mediterranean sole population is led primarily by neutral processes because of low connectivity due to spatial segregation and limited dispersal, but it also suggests the presence of local adaptation. These results should be taken into account to support and optimize the assessment of stock units, including a review and possible redefinition of fishery management units.

The Frequency of Intermediate Alleles in Patients with Cerebellar Phenotypes - Elena Capacci; Silvia Bagnoli; Giulia Giacomucci; Costanza Maria Rapillo; Alessandra Govoni; Valentina Bessi; Cristina Polito; Irene Giotti; Alice Brogi; Elisabetta Pelo; Sandro Sorbi; Benedetta Nacmias; et al. (The Cerebellum, 2023)
Cerebellar syndromes are clinically and etiologically heterogeneous and can be classified as hereditary, neurodegenerative non-hereditary, or acquired. Few data are available on the frequency of each form in the clinical setting. Growing interest is emerging regarding the genetic forms caused by triplet repeat expansions. Alleles with repeat expansion lower than the pathological threshold, termed intermediate alleles (IAs), have been found to be associated with disease manifestation. In order to assess the relevance of IAs as a cause of cerebellar syndromes, we enrolled 66 unrelated Italian ataxic patients and described the distribution of the different etiology of their syndromes and the frequency of IAs. Each patient underwent complete clinical, hematological, and neurophysiological assessments, neuroimaging evaluations, and genetic tests for autosomal dominant cerebellar ataxia (SCA) and fragile X-associated tremor/ataxia syndrome (FXTAS). We identified the following diagnostic categories: 28% sporadic adult-onset ataxia, 18% cerebellar variant of multiple system atrophy, 9% acquired forms, 9% genetic forms with full-range expansion, and 12% cases with intermediate-range expansion. The IAs were six in the FMR1 gene, two in the gene responsible for SCA8, and one in the ATXN2 gene. The clinical phenotype of patients carrying the IAs resembles, in most of the cases, the one associated with full-range expansion. Our study provides an exhaustive description of the causes of cerebellar ataxia, estimating for the first time the frequency of IAs in SCAs- and FXTAS-associated genes. The high percentage of cases with IAs supports further screening among patients with cerebellar syndromes.

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Packaging contaminants in former food products: Using Fourier Transform Infrared Spectroscopy to identify the remnants and the associated risks - Sharon Mazzoleni; Stefano Magni; Marco Tretola; Alice Luciano; Luca Ferrari; Cristian Edoardo Maria Bernardi; Peng Lin; Matteo Ottoboni; Andrea Binelli; Luciano Pinotti (Journal of Hazardous Materials, 2023)

Commercial sharks under scrutiny: Baseline genetic distinctiveness supports structured populations of small-spotted catsharks in the Mediterranean Sea - Riccardo Melis; Laura Vacca; Alessia Cariani; Laura Carugati; Alessandro Cau; Charis Charilaou; Simone Di Crescenzo; Alice Ferrari; Maria Cristina Follesa; Farid Hemida; Sarah Helyar; Sabrina Lo Brutto; et al. (Frontiers in Marine Science, 2023)
The present study, based on microsatellite markers, describes a population genetic analysis of the small-spotted catshark Scyliorhinus canicula (Linnaeus, 1758), representing one of the most abundant and commonly caught cartilaginous fishes in the Mediterranean Sea and adjacent areas. The analyses were performed to unravel the genetic features (variability, connectivity, sex-biased dispersal) of their relative geographic populations, both at the small (around the coast of Sardinia, Western Mediterranean Sea) and at a larger spatial scale (pan-Mediterranean level and between the Atlantic Ocean and the Mediterranean Sea). Individual clustering, multivariate and variance analyses rejected the hypothesis of genetic homogeneity, with significant genetic differences mainly within the Mediterranean between the Western and Eastern basins, as well as between the Mediterranean and the NE Atlantic Ocean. In detail, our results seem to confirm that the Strait of Gibraltar could not represent a complete barrier to the exchange of individuals of small-spotted catshark between the Atlantic Ocean and the Mediterranean Sea. In the latter area, a complex genetic structuring for S. canicula was found. Apart from differences among the Western, Eastern and Adriatic sites, within the Western basin the small-spotted catsharks around Sardinian waters are strongly differentiated from all others (both from the eastern Tyrrhenian Sea and southernmost part of the Algerian basin) and are demographically stable. Several possible mechanisms, both biological and abiotic (e.g., migratory behavior, waterfronts, and oceanographic discontinuities), are discussed here to explain their peculiar characteristics. Overall, the genetic data presented, both at the local and regional level, could represent a baseline information, useful for the temporal monitoring of populations, and to assess the effects of present or future fishing/management/conservation measures.

First evidence of population genetic structure of the deep-water blackmouth catshark Galeus melastomus Rafinesque, 1810 - Simone Di Crescenzo; Alice Ferrari; Claudio Barría; Rita Cannas; Alessia Cariani; Jim Drewery; Lourdes Fernández-Peralta; Daniela Giordano; Manuel Hidalgo; Vasiliki Kousteni; Ilaria Anna Maria Marino; Daniela Massi; et al. (Frontiers in Marine Science, 2022)
Among the main measures adopted to reduce anthropogenic impacts on elasmobranch communities, understanding the ecology of deep-sea sharks is of paramount importance, especially for potentially vulnerable species highly represented in the bycatch composition of commercial fisheries such as the blackmouth catshark Galeus melastomus . In the present work, we unravelled the first indication of population genetic structure of G. melastomus by using a novel and effective panel of nuclear, and polymorphic DNA markers and compared our results with previous findings supporting high genetic connectivity at large spatial scales. Given the lack of species-specific nuclear markers, a total of 129 microsatellite loci (Simple Sequence Repeats, SSRs) were cross-amplified on blackmouth catshark specimens collected in eight geographically distant areas in the Mediterranean Sea and North-eastern Atlantic Ocean. A total of 13 SSRs were finally selected for genotyping, based on which the species exhibited signs of weak, but tangible genetic structure. The clearcut evidence of genetic differentiation of G. melastomus from Scottish waters from the rest of the population samples was defined, indicating that the species is genetically structured in the Mediterranean Sea and adjacent North-eastern Atlantic. Both individual and frequency-based analyses identified a genetic unit formed by the individuals collected in the Tyrrhenian Sea and the Strait of Sicily, distinguished from the rest of the Mediterranean and Portuguese samples. In addition, Bayesian analyses resolved a certain degree of separation of the easternmost Aegean sample and the admixed nature of the other Mediterranean and the Portuguese samples. Here, our results supported the hypothesis that the interaction between the ecology and biology of the species and abiotic drivers such as water circulations, temperature and bathymetry may affect the dispersion of G. melastomus , adding new information to the current knowledge of the connectivity of this deep-water species and providing powerful tools for estimating its response to anthropogenic impacts.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Anadara kagoshimensis (Mollusca: Bivalvia: Arcidae) in Adriatic Sea: morphological analysis, molecular taxonomy, spatial distribution, and prediction - PIERLUIGI STRAFELLA; ALICE FERRARI; GIANNA FABI; VERA SALVALAGGIO; ELISA PUNZO; CLARA CUICCHI; ANGELA SANTELLI; ALESSIA CARIANI; FAUSTO TINTI; ANNA NORA TASSETTI; GIUSEPPE SCARCELLA (Mediterranean Marine Science, 2017)
Morphological analysis, molecular characterization, and information on distribution and density of Anadara kagoshimensis (Tokunaga, 1906) specimens collected in the Adriatic Sea were here carried out as based on various material and data from five surveys conducted from 2010 to 2014, for a total of 329 bottom trawl hauls. The morphological and molecular analyses allowed to clarify the confused taxonomy regarding the biggest ark clam alien species invading the Italian waters and the Mediterranean Sea. The analysis on distribution and density revealed that A. kagoshimensis mostly occurs along the Italian coast at depths from 8 to 50 m, with a catch frequency of more than 98% in all hauls performed on silty-clay sediment at 8-30 m depth. The hotspot map clearly shows a reduction of its distribution area from 2010 to 2012.

Automatic imitation of the arm kinematic profile in interacting partners - Alessandro D’Ausilio; Leonardo Badino; Pietro Cipresso; Alice Chirico; Elisabetta Ferrari; Giuseppe Riva; Andrea Gaggioli (Cognitive Processing, 2015)

Stock boundaries of Mullus barbatus (Mullidae) and Parapenaeus longirostris (Penaeidae) populations in the Italian seas: development of genomic 2b-RAD markers - Ferrari Alice (Frontiers in Marine Science, 2014)

Chromosome numbers and meiotic analysis in the pre-breeding of Brachiaria decumbens (Poaceae) - GLÉIA CRISTINA LAVERDE RICCI; ALICE MARIA DE SOUZA-KANESHIMA; MARIANA FERRARI FELISMINO; ANDREA BEATRIZ MENDES-BONATO; MARIA SUELY PAGLIARINI; CACILDA BORGES DO VALLE (Journal of Genetics, 2011)